A Comparative Study of the Chemical Composition and Nutritional Value of Muscles in Different Zones in the Body of two Species of Teleosts; Greenback Mullet, Planiliza subviridis (Valenesciennes, 1836) and Abu Mullet, Planiliza abu (Heckel, 1843) - Akeil Jameil Mansour (Journal of Global Pharma Technology, 2018)
The current study was conducted to estimate the chemical composition of the muscles of different regions in the body of the studied fish to assess the nutritional value of their muscles .The fish studied included two species of teleosts fish belonging to the Mugilidea family ; Greenback mullet , Planiliza subviridis (Valeneciennes , 1836) and Abu mullet , Planiliza abu (Heckel, 1843).The components of the chemical composition of the muscles included: protein, fat, moisture and ash as well as to estimate the nutritional value (energy) of both protein and fat content. Samples were collected from the Qurna market - north of Basra - Iraq in August / 2018.The results showed differences in the values of the chemical composition of the muscles of the two studied species. The values of protein content ranged between 20.54 - 20.10% and 19.53-18.32% in P. subviridis and P. abu respectively, while the lipid content values ranged between 3.76-5.76% P .subviridis while ranged between 5.43- 7.72% in P. abu. The moisture content had higher values ranging between 71.08 - 70.17% and 71.84 - 70.17% in P. subviridis and P.abu respectively while the ash content ranged between 2.57 - 2.30% and 2.80 - 2.55% in P. subviridis and P. abu Respectively. The results showed that total energy value in P. subviridis were 124.12KCal / g compared to P. abu which recorded 134.9 kcal / g .The statistical results indicated positive relationship between fish weight and protein , lipid and ash content in the studied fish, while there was an inverse relationship between moisture content and fish weight in the studied species. The statistical results showed no significant differences P>0.05 between the protein, moisture and ash content in two body regions in the studied species, while revealed significant differences P<0.05 in lipid content in the studied fish.Keywords: Planiliza subviridis, Planiliza abu, Fish muscles, Chemical composition.